RECONSTRUCTION OF THE FINANCIAL REPORT PREPARATION ON BUM NAGARI BERSAMA LKD LENGGOGENI IN SUNGAI TARAB DISTRICT IN 2024 BASED ON MINISTER OF VILLAGES, DEVELOPMENT OF DISADVANTAGED REGIONS, AND TRANSMIGRATION REGULATION NO. 136 OF 2022 - Abdul Rauf; Sri Adella Fitri; Mega Rahmi; Nita Fitria; Khairul Marlin (Jurnal Akuntansi Syariah (JAkSya), 2025)
The reconstruction of financial statement preparation aims to improve and enhance the quality of financial reporting in accordance with the Minister of Villages, Development of Disadvantaged Regions, and Transmigration Regulation No. 136 of 2022. Financial statements must be prepared accurately and meet the criteria of understandability, relevance, reliability, and comparability, thereby providing a positive impact on the development of BUM Nagari Bersama LKD Lenggogeni in Sungai Tarab District and supporting managerial decision-making. This study employs a qualitative case study through field research using a descriptive and participatory approach involving the management, beginning with an initial survey and focus group discussion (FGD). Primary data were obtained from semi-structured interviews with the management of BUM Nagari Bersama LKD Lenggogeni, while secondary data were collected from financial transaction documentation for one accounting period, financial statements, and other supporting documents. Data analysis was conducted using thematic analysis, and source triangulation was applied to enhance data validity and reliability. The findings indicate that financial management, which had previously been poorly organized, was successfully reconstructed in a systematic manner and in compliance with applicable regulations. The reconstructed financial statements consist of an income statement, statement of changes in equity, statement of financial position, and cash flow statement.